Phone Usage Time Monitoring System Personal Computer Based - Rera Mahendra Asyafata (Institute of Computer Science (IOCS), 2022)
The telephone is a practical, easy, fast, and reliable means of communication. However, when using the telephone, problems often arise in terms of costs. The lack of control over telephone users in using pulses is one of the obstacles, because then telephone pulses do not feel a dramatic increase from the initial calculation. Telephone data recording technology that uses the DTMF (Dual Tone Multiple Frequency) method and PPI 8255 as an interface can be used to overcome this. We can use this technology application to create a tool that can monitor telephone usage time through a Personal Computer. So that by doing so, home telephones or government and private institutions are protected from spikes in credit usage. From this final project obtained a monitoring system for telephone usage through a Personal Computer both for incoming and outgoing calls in terms of data recording and usage time. This system can also limit or block unwanted outgoing telephone numbers at any time without having to stand by the phone.